The The Role of Tribe Headman in Kg. Semelor, Malaysia in Disseminating Tuberculosis Knowledge Amongst the Temiar Indigenous Community - Mokhtar, Khairiah Salwa; Nurulhasanah Abdul Rahman (Advances in Humanities and Contemporary Studies, 2021)
Despite the increasing prevalence of Tuberculosis (TB) infection in Malaysia, data documenting Indigenous people (i.e. Orang Asli) afflicted by the disease remains scarce. Geography-wise, Orang Asli in Malaysia traditionally live in forest land or remotely, often faces many impediments on access to natural resources, basic infrastructure, and healthcare services. Consequently, the role played by Tok Batin as the Tribe Headman is crucial as a mediator between the government and community, as Orang Asli highly respect their leader and is dependent upon leadership decisions. Here, 11 participants were interviewed using purposive sampling, whereby the transcripts were then subjected to categorisation via thematic analysis. Accordingly, four themes emerged related to the general belief of the Temiar community, understanding TB disease, reliance on the Tribe Headman, and acceptance of modern medication. Addressing Orang Asli and infectious diseases’ issues were significant towards maximising their health outcomes and improving the national TB control in Malaysia.